2010
DOI: 10.1007/s11199-009-9727-0
|View full text |Cite
|
Sign up to set email alerts
|

The Sexual Double Standard and Gender Differences in Predictors of Perceptions of Adult-Teen Sexual Relationships

Abstract: We study gender differences and the effects of adult's gender, an authority gap, and an age gap on university students' perceptions of adult-teen sexual relationships. We specifically examine: the adult's criminality, damage to the teen's reputation, and emotional damage to the teen. We use a sample of 2,871 students from a Southwestern university in the U.S. who judged vignettes describing an adult-teen encounter. OLS regression demonstrated that women judged the scenarios more negatively than men. Further an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 34 publications
2
37
1
Order By: Relevance
“…Further analyses revealed that negative perceptions and emotions partially mediated the significant relationship between younger partner age and disapproval of the older partner's behavior (Horvath & Giner-Sorolla, 2007). The second study by Sahl and Keene (2010) revealed similar results. A large, representative university sample of undergraduate and graduate students read about a statutory rape case involving a 15-year-old adolescent and a partner who was either 7 years older (i.e., 22 years old) or 27 years older (i.e., 42 years old).…”
Section: Partner Age Gapsmentioning
confidence: 56%
See 4 more Smart Citations
“…Further analyses revealed that negative perceptions and emotions partially mediated the significant relationship between younger partner age and disapproval of the older partner's behavior (Horvath & Giner-Sorolla, 2007). The second study by Sahl and Keene (2010) revealed similar results. A large, representative university sample of undergraduate and graduate students read about a statutory rape case involving a 15-year-old adolescent and a partner who was either 7 years older (i.e., 22 years old) or 27 years older (i.e., 42 years old).…”
Section: Partner Age Gapsmentioning
confidence: 56%
“…Women also reported higher levels of negative emotions (e.g., anger and disgust) and greater perceived harm to the younger partner than men. Sahl and Keene (2010) found that, compared to men's perceptions, women's perceptions of damage to a teen partner's reputation were significantly more likely to be affected by the age gap between partners. These findings are corroborated by a robust and consistent body of research examining respondent gender differences in perceptions of child-adult and adolescent-adult sexual abuse cases (for a review, see Bottoms, Golding, Wiley, Stevenson, & Wozniak, 2007).…”
Section: Respondent Gendermentioning
confidence: 83%
See 3 more Smart Citations